Regional cooperation in South Asia : problems & prospects - Prasad, Bimal, 1925- (New Delhi : Vikas Pub. House, 1989)
Contributed papers.
Includes bibliographies and index.
Keywords: South Asian Association for Regional Cooperation; South Asian cooperation